A literature review on local patent applications for corrosion inhibitors development used in the protection of ferrous and non-ferrous types of surfaces - Abdullah, Fatin Nabilah (2017)
The phenomenon of corrosion appears in various industrial applications and responsible for numerous losses in industries around the world. Corrosion affects the durability of the infrastructure assets and industrial equipments. Thus, this phenomenon remains as a major concern in industries around the world. Corrosion inhibitor is known as the best methods to prevent degradation of metal surface as it can prevent or control corrosion process by selection of highly corrosion resistant materials where it must be suitable to the operating conditions. Corrosion inhibitors are used in a wide range of industrial applications such as oil and gas industries, cooling water system, reinforced concrete, paints, lubricants and more. Corrosion inhibitor particularly extends the life of the infrastructure and industrial equipments therefore saving large expenses in materials equipment and structures. This review is an analysis of the number of local patents applications for corrosion inhibitor development used in the protection of ferrous and non-ferrous types of surface.